Assessment of Agricultural Practices for Controlling Fusarium and Mycotoxins Contamination on Maize Grains: Exploratory Study in Maize Farms - Simões, Daniela (2023)
Maize is a significant crop to the global economy and a key component of food and feed, although grains and whole plants can often be contaminated with mycotoxins resulting in a general exposure of the population and animals. To investigate strategies for mycotoxins control at the grain production level, a pilot study and exploratory research were conducted in 2019 and 2020 to compare levels of mycotoxins in grains of plants treated with two fertilizers, F-BAC and Nefusoil, under real agricultural environment. The 1650 grains selected from the 33 samples were assessed for the presence of both Fusarium species and mycotoxins. Only fumonisins and deoxynivalenol were detected. Fumonisin B1 ranged from 0 to 2808.4 µg/Kg, and fumonisin B2 from 0 to 1041.9 µg/Kg, while deoxynivalenol variated from 0 to 465.8 µg/Kg. Nefusoil showed to be promising in regard to fumonisin control. Concerning the control of fungal contamination rate and the diversity of Fusarium species, no significant differences were found between the two treatments in any of the years. However, a tendency for was observed Nefusoil of lower values, probably due to the guaranteed less stressful conditions to the Fusarium spp. present in the soil, which do not stimulate their fumonisins production.